2017
DOI: 10.5114/wo.2017.68616
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between mesenchymal stem cells and macrophages in inflammatory bowel disease and associated colorectal cancer

Abstract: Mesenchymal stem cells (MSCs) are attractive seed cells for immunotherapy, tissue engineering and regenerative medicine due to their self-renewal and multidirectional differentiation abilities, diverse immunoregulatory functions and ease of isolation from a wide range of tissues. MSCs exert their immunoregulatory effect on immune cells via cell-to-cell contact and paracrine mechanisms. In turn, MSCs can also be modulated by immune cells. Macrophages are constantly present in the mucosa of the intestinal tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 93 publications
0
13
0
1
Order By: Relevance
“…Our results further suggest that when IFN-γ priming of MSCs is followed with exposure to inflammatory macrophages, the enhanced immunomodulation is maintained. This is important because there is opposing evidence of crosstalk between MSC and macrophages in wound repair and cancer studies [ 42 44 ], which results in altered phenotype and function. Inflammatory licensing with poly I:C resulted in only modest improvement in MSC immunomodulatory function and gene expression changes compared to that observed with IFN-γ stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further suggest that when IFN-γ priming of MSCs is followed with exposure to inflammatory macrophages, the enhanced immunomodulation is maintained. This is important because there is opposing evidence of crosstalk between MSC and macrophages in wound repair and cancer studies [ 42 44 ], which results in altered phenotype and function. Inflammatory licensing with poly I:C resulted in only modest improvement in MSC immunomodulatory function and gene expression changes compared to that observed with IFN-γ stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MSCs have attracted great interest for clinical application in treating various inflammatory diseases. Some studies have already demonstrated the beneficial effects of MSCs in ameliorating various inflammatory disorders, including sepsis, inflammatory bowel disease and experimental allergy encephalomyelitis [ 7 , 8 , 27 , 29 ]. However, therapeutic effects were not always achieved [ 8 , 26 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, stem cell-derived exosomes have demonstrated significant therapeutic benefits in several diseases. Mao et al (2017a) showed that mesenchymal stem cell (MSC)-derived exosomes could relieve the symptoms of IBD and helped in the recovery of damaged tissues and organs.…”
Section: Sources Of Exosomesmentioning
confidence: 99%